Renal stress and kidney injury biomarkers in response to endurance cycling in the heat with and without ibuprofen - McDermott, B. P.; Smith, C. R.; Butts, C. L.; Caldwell, A. R.; Lee, E. C.; Vingren, J. L.; Munoz, C. X.; Kunces, L. J.; Williamson, K.; Ganio, M. S.; Armstrong, L. E. (Journal of Science and Medicine in Sport, 2018)
Exercise, especially in the heat, can contribute to acute kidney injury, which can expedite chronic kidney disease onset. The additional stress of ibuprofen use is hypothesized to increase renal stress. OBJECTIVES: To observe the effects of endurance cycling in the heat on renal function. Secondarily, we investigated the effect of ibuprofen ingestion on kidney stress. DESIGN: Randomized, placebo controlled and observational methods were utilized. METHODS: Forty cyclists (52±9y, 21.7±6.5% body fat) volunteered and completed an endurance cycling event (5.7±1.2h) in the heat (33.2±5.0°C, 38.4±10.7% RH). Thirty-five participants were randomized to ingest a placebo (n=17) or 600mg ibuprofen (n=18) pre-event. A blood sample was drawn before and following the event. Serum creatinine was assessed by colorimetric assay. An ELISA was used to measure serum neutrophil gelatinase-associated lipocalin. Fractional excretion of sodium was calculated after urinary and serum electrolyte analyses. RESULTS: Placebo versus ibuprofen groups contributed no significant difference in any variable (p>0.05). Serum creatinine significantly increased from pre- (0.52±0.14mg/dL) to post-event (0.88±0.21mg/dL; p<0.001). Serum neutrophil gelatinase-associated lipocalin significantly increased (pre: 68.51±17.54ng/mL; post: 139.12±36.52ng/mL; p<0.001) and fractional excretion of sodium was significantly reduced from pre- (0.52±0.24%) to post-event (0.27±0.18%; p<0.001). CONCLUSIONS: Changes in renal biomarkers suggest mild acute kidney injury and reduced kidney function during a single bout of endurance cycling in the heat, without influence from moderate ibuprofen ingestion. ABSTRACT FROM AUTHOR